Capacity Building and Business Development of Redchic Accessories through a Participatory Action Research-Based University Community Engagement Program - Indah Maya Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
Creative Micro, Small, and Medium Enterprises (MSMEs) often face operational and administrative constraints that impede their market survival. Redchic Accessories, a small business specializing in fashion accessories, experienced operational inefficiencies, irregular bookkeeping, and traditional marketing bottlenecks. This study aimed to evaluate the effectiveness of a university-led capacity-building program in improving business management, financial accountability, operational efficiency, and digital marketing of Redchic Accessories. Utilizing a Participatory Action Research (PAR) approach across sequential planning, action, and reflection cycles, the team engaged the business owner and 3 key employees over a 4-month intervention period. The framework focused on instituting standardized operating procedures (SOPs), deploying digital bookkeeping ledger spreadsheets, and optimizing online storefront architectures. Quantitative operational monitoring revealed that the intervention minimized production cycle delays from a baseline of 4 days down to 1.5 days, reduced raw material wastage by 28%, achieved a 100% monthly financial recording completion rate, and drove an 18.5% growth in marketplace traffic. In conclusion, the participatory intervention substantially improved managerial practices and established a stronger foundation for sustainable business development.